2‐Dimensional Transition Metal Dichalcogenides with Tunable Direct Band Gaps: MoS2(1–x)Se2x Monolayers. (12th December 2013) - Mann, John; Ma, Quan; Odenthal, Patrick M.; Isarraraz, Miguel; Le, Duy; Preciado, Edwin; Barroso, David; Yamaguchi, Koichi; von Son Palacio, Gretel; Nguyen, Andrew; Tran, Tai; Wurch, Michelle; et al.
<x xml:space="preserve">Abstract</x> MoS2(1−x) Se2x single‐layer films are prepared using a mixture of organic selenium and sulfur precursors as well as a solid molybdenum source. The direct bandgaps are found to scale nearly linearly with composition in the range of 1.87 eV (pure single‐layer MoS2) to 1.55 eV (pure single‐layer MoSe2) permitting straightforward bandgap engineering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>